The flora of renal haemodialysis shunt sites. Issue 1 (January 1975) - Rebel, M H; Van Furth, R; Stevens, P; Bosscher-Zonderman, L; Noble, W C
Abstract : During investigations of the microbial flora of the skin over haemodialysis shunt sites it has not proved possible to predict clinical infection by a preceding colonization of the shunt site with a pathogenic organism. The normal non-pathogenic flora of the sites is not specifically related to the flora of other sites on the body though Staphylococcus aureus on a shunt site appeared to be acquired principally from the nose when the shunt was in the arm or from the perineum when the shunt was in the leg. Cimino shunt sites had a greater density of organisms than did Scribner shunt sites; this may be related to the disinfection procedures.